PENGARUH PIJAT OKSITOSIN TERHADAP INVOLUSI UTERI PADA IBU POST PARTUM DI PUSKESMAS PAKUAN BARU DAN BIDAN PRAKTIK MANDIRI (BPM) di JAMBI - Susi Widiawati; Ezalica Puji Utami (Universitas Malahayati Lampung, 2020)
Introduction: Postpartum mothers will experience two things, namely uterine involution and lactation. Uterine invalution is influenced by several factors, one of which is the hormone oxytocin. Good validation can prevent postpartum hemorrhage. Postpartum hemorrhage is one factor of postpartum maternal mortality.Purpose: To determine the effect of oxytocin massage on uterine involution in postpartum mothersMethod: This study was a quasy experiment with a two group pre posttest design. The study was conducted at the Pakuan New Care Health Center and BPM Jambi. Sampling with a purposive sampling method, the sample used (12 intervention groups and 12 control groups). The instruments in the study used observation sheets. Data were analyzed using the Wilcoxon Test.Results: The height of the fundus of the intervention group was 6 hours postpartum with a median value of 11.5750 cm with a standard deviation of 0.30521. Whereas for 6 days postpartum with a median value of 5.5650 cm with a standard deviation of 0.04338. The height of the uterine fundus of the control group at 6 hours postpartum with a median value of 12.0000 cm with a standard deviation of 0.28789. Whereas for 6 days postpartum with a median value of 6.2250 cm with a standard deviation of 0.22191, the bivariate analysis was p-value 0.002.Conclusion: There is an effect of oxytocin massage on uterine involution in postpartum mothers at the Pakuan New Care Health Center and BPM Jambi in 2018. It is recommended that the leaders of the Pakuan New Care Health Center and PBM be able to make a policy on Oxytocin massage carried out by health workers (nurses and midwives) to postpartum mothers. Keywords: Oxytocin Massage, Uterine Involution